2015
DOI: 10.1177/1010539515582220
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Among Adolescents in an East Malaysian Rural Indigenous Community

Abstract: This study explores the rural environmental factors that influence adolescents' participation in physical activities (PA). Thirty-six indigenous adolescents, aged 13 to 17 years from rural communities of East Malaysia were involved in the photovoice procedures: photo-taking, selecting, contextualizing, and codifying themes. Despite being endowed with natural resources such as river, forest, hills, and so on, the adolescents and the community did not capitalize on these rich resources to promote and engage in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In general, the associated factors of PA include environmental, social, psychosocial and cultural characteristics. 26 27 The data from the in-depth interviews showed a variety of those characteristics among the medical students. The common findings, identified through the interviews, showed that medical students needed social support to participate in PA behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the associated factors of PA include environmental, social, psychosocial and cultural characteristics. 26 27 The data from the in-depth interviews showed a variety of those characteristics among the medical students. The common findings, identified through the interviews, showed that medical students needed social support to participate in PA behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…12 Safety threats around neighborhood areas may have a negative impact on the opportunities for children and adolescents to play at outdoor areas. 13,14 The availability and accessibility of playgrounds, recreational parks and environment settings were suggested as possible correlates for the physical activity of preschoolers. 15 Although previous studies have investigated the association of barriers, motivators, and environmental factors with the physical activity level of preschoolers 11,16 , little is known about whether these barriers, motivators, and environmental factors differ by sociodemographic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental plays an essential role in the involvement of physical activity. Even for the rural indigenous community locally and worldwide, lack of physical activity was observed due to poor maintenance of natural resources and limited access to space and facilities that support an active lifestyle in their settlement, which has implications for NCDs risk later in life 35,36 .…”
Section: Discussionmentioning
confidence: 99%